2022
DOI: 10.31234/osf.io/u2tbh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socioeconomic Status and Childhood Sleep: A Systematic Review and Meta-Analysis

Abstract: Context: Socioeconomic status (SES) is increasingly understood to be a key contributor to sleep health, but the research in childhood has not been synthesized.Objective: To examine the associations between indicators of child SES and child sleep (≤18 years old), we conducted a systematic review and meta-analyses. Data Sources: CINAHL with Full Text, PsycINFO, and MEDLINE/PubMed were searched using terms to define SES and childhood to ascertain all relevant, peer-reviewed articles from database inception to 27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Social characteristics refer to factors such as neighbourhood deprivation (i.e., low socioeconomic status (SES) (14), disorder (i.e., incivility, deterioration, crime) (15), social capital (16), and ethnic composition (12,17). Extant research has found strong associations between neighbourhood characteristics, particularly deprivation, with physical, behavioural, and mental health outcomes in children (18)(19)(20)(21). Children in disadvantaged neighbourhoods (i.e., lower SES and poor physical conditions) on average were at higher odds of experiencing obesity (22), having poor peer relations (23), lower cognitive development (24, 25) and more mental health concerns (26).…”
Section: Introductionmentioning
confidence: 99%
“…Social characteristics refer to factors such as neighbourhood deprivation (i.e., low socioeconomic status (SES) (14), disorder (i.e., incivility, deterioration, crime) (15), social capital (16), and ethnic composition (12,17). Extant research has found strong associations between neighbourhood characteristics, particularly deprivation, with physical, behavioural, and mental health outcomes in children (18)(19)(20)(21). Children in disadvantaged neighbourhoods (i.e., lower SES and poor physical conditions) on average were at higher odds of experiencing obesity (22), having poor peer relations (23), lower cognitive development (24, 25) and more mental health concerns (26).…”
Section: Introductionmentioning
confidence: 99%